Gallium-containing mesoporous nanoparticles influence in-vitro osteogenic and osteoclastic activity - Kurtuldu, Fatih; Mutlu, Nurshen; Friedrich, Ralf P.; Beltrán, Ana M.; Liverani, Liliana; Detsch, Rainer; Alexiou, Christoph; Galusek, Dušan; Boccaccini, Aldo R. (Biomaterials Advances, 2024)
Mesoporous silica nanoparticles were synthesized using a microemulsion-assisted sol-gel method, and calcium, gallium or a combination of both, were used as dopants. The influence of these metallic ions on the physicochemical properties of the nanoparticles was investigated by scanning and transmission electron microscopy, as well as N2 adsorption-desorption methods. The presence of calcium had a significant impact on the morphology and textural features of the nanoparticles. The addition of calcium increased the average diameter of the nanoparticles from 80 nm to 150 nm, while decreasing their specific surface area from 972 m2/g to 344 m2/g. The nanoparticles of all compositions were spheroidal, with a disordered mesoporous structure. An ion release study in cell culture medium demonstrated that gallium was released from the nanoparticles in a sustained manner. In direct contact with concentrations of up to 100 μg/mL of the nanoparticles, gallium-containing nanoparticles did not exhibit cytotoxicity towards pre-osteoblast MC3T3-E1 cells. Moreover, in vitro cell culture tests revealed that the addition of gallium to the nanoparticles enhanced osteogenic activity. Simultaneously, the nanoparticles disrupted the osteoclast differentiation of RAW 264.7 macrophage cells. These findings suggest that gallium-containing nanoparticles possess favorable physicochemical properties and biological characteristics, making them promising candidates for applications in bone tissue regeneration, particularly for unphysiological or pathological conditions such as osteoporosis.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Bioactive glasses; Gallium; Mesoporous silica nanoparticles; Osteoblast; Osteoclast